Fracture of the Tibial Baseplate 16 Years after Miller-Galante II Total Knee Arthroplasty - Kazuaki Mineta; Masahiko Okada; Soshi Matsumoto; Daisuke Hamada; Tomohiro Goto; Koichi Sairyo (Case Reports in Orthopedics)
We report a rare case of tibial baseplate fracture of Miller-Galante II (MG II) prosthesis. We examine the factors that may cause such late fracture and review the literature on radiographic analysis and retrieval studies. A 76-year-old woman, who had undergone bilateral MG II total knee arthroplasty due to rheumatoid arthritis 16 years earlier, presented to our department with a 3-month history of left knee pain. Plain radiographs revealed severe distortion of the medial tibial component. During revision knee arthroplasty, we observed severe metallosis in the knee joint, polyethylene insert deformation, and posteromedial coronal baseplate fracture. After removal of the fractured tray, a bone deficit due to osteolysis was noted. The revision prosthesis (LCCK, Zimmer-Biomet) was implanted uneventfully. Four months after revision surgery, the patient was ambulating and had no complications. The implants on the right side had survived without complications for 17 years. We speculate that the primary causative factor of the fatigue fracture of the base plate due to loss of bony support most likely secondary to osteolysis was varus malalignment at primary implantation. This case highlights the importance of paying close attention to the correct alignment of each component at primary implantation.